PURE ISLAM AND ENLIGHTENMENT AGAINST IGNORANCE - Khodjiqurbonova Shahrizoda (Educational Research in Universal Sciences, 2022)
In this article, we will talk about those who misinterpreted Islam and the “heroes” who helped them to come to this opinion. “No matter how much a mountain is hurt with a goat's horn, the mountain cannot be hurt in the slightest” in this we should understand that no matter how much harm is done to the religion, it does not lose itself.